Vietnam Agriculture Finance Diagnostic Report : Financial Inclusion Support Framework – Vietnam Country Support Program - World Bank (World Bank, Washington, DC, 2020)
Agriculture remains economically and socially important in Vietnam despite agriculture’s declining share of gross domestic product (GDP). The share of primary agricultural activity in the GDP has fallen to 13 percent, compared with more than 30 percent two decades ago. The active labor force in agriculture remains as high as 45 percent. Chapter one presents an overview of the agriculture and financial sectors. Chapter two presents an analysis of farmers` financial access and use of financial services. Chapter three discusses key trends in agriculture credit and agriculture insurance markets. Chapter four discusses the key institutions and instruments of public sector support for agriculture finance. Chapter five identifies key challenges that are constraining the growth of agriculture finance, and lastly, chapter six identifies major opportunity areas and makes key recommendations to capitalize on the identified opportunities.